Investigation of host liquid crystal composition on polymer stabilised blue phase properties - Mohd Said, S.; Rahman, M.A.; Yamana, I.; Kimura, M. (2014)
Polymer stabilised blue phase liquid crystals (PSBPLCs) have been investigated for photonics and display applications for the following reasons: optical isotropy in the dark state, ease of fabrication due to the omission of the alignment layer, and sub-millisecond response length. Major barriers to the commercialisation of PSBPLCs are: hysteresis, residual birefringence, and most significantly, high driving voltage. We have chosen to lower the driving voltage through optimization of the mixture (host LC, chiral dopant and monomer). In this paper, investigation of the contribution of the host liquid crystal to the phase stability and electro-optic characteristics of the PSBP will be discussed. The following cases have been investigated: a) A three component host liquid crystal (E8, PE-sCNF (4- Cyano-3-fluorophenyl 4-pentyl benzoate) and CPP-3FF (4-(trans-4-n-propyl cyclohexyl)-3',4'-difluoro-l,l'- biphenyl), LCC Corporation, Japan). For a ratio of E8:PE-CNF:CPP-3FF of 5:3:2, a large BPI window of >SO.4°C and low hysteresis was achieved, but the driving voltage was 79V, and b) A single host liquid crystal, 80CB with chiral dopant Clsl S. For a ratio for 80CB:CBls of 1:1, this mixture demonstrated a significantly lower driving voltage of 6SV, but exhibited a smaller BPI window of >27°C. Decrease in the ratio of 80CB:CBls also induced the presence of a BPII phase in the mixture. A single host liquid crystal has the advantage of simplicity of composition, and lowered driving voltage. However, the hysteresis and blue phase temperature range needs to be optimised. This investigation concludes upon the suggestion of liquid crystal characteristics which optimises the blue phase temperature range, low hysteresis, switching times and driving voltage.